Hexagonal network cat paw-inspired iongel composites improve tribological properties - Khan Rajib Hossain; Xinle Yao; M. Abdul Jalil; Xiaolong Wang (Journal of Ionic Liquids)
Biomimetic surfaces, inspired by nature, are gaining popularity due to their promising technological applications. Traditional microfabrication techniques face difficulties due to the intricacy of hexagonal microstructures. We successfully developed a bioinspired surface pattern resembling cat paws using innovative 3D laser lithography. Our composite material, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, inspired by the natural architecture of cat paws with their passive capability for biomechanical damping, enables increased dissipation and tribological performance. The iongel surface shows shape memory, resistance to creep properties, stiffness controllability, and self-lubricating behavior under dynamic loading conditions. Mechanical testing demonstrates reduced hysteresis behavior and an increase in energy absorption on PU surfaces with an average friction reduction of ∼9.8 % ± 1.2 %, using the same test conditions (n=3). We clarify the multiscale deformation mechanisms using an in-depth investigation, including finite element simulations. These methods greatly improve the material's tribological performance and show that hydrogel-like networks of fibers and membranes hold the matrix together. These composite materials have great potential for use in sports safety equipment and various engineering domains because of their flexible and soft hexagonal network structure, representing cat paws.